2021
DOI: 10.1186/s13071-021-04723-4
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of hepatitis E virus and Plasmodium falciparum malaria: A genuine risk in sub-Saharan Africa

Abstract: Background There is a high prevalence of malaria and viral hepatitis in South Africa. Co-infection with Plasmodium malaria (leading to cerebral malaria) and hepatitis E virus (HEV) is a rare phenomenon. Case presentation A 33-year-old African American male with no past medical history developed altered mental status on his return from Ivory Coast. His blood tests were significant for renal and liver failure and a high Plasmodium parasite burden of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…reported that chronic HEV infection might occur in HIV-infected patients and is associated with active hepatitis ( Dalton et al., 2009 ). There are also cases of HEV superinfection with hepatitis A, hepatitis B, hepatitis C, Campylobacter jejuni , Giardia intestinalis , or malaria, which indicates that HEV infection may exacerbate liver damage, accelerate disease progression, and increase mortality in patients with cirrhosis or chronic liver disease ( Lorenzo et al., 2016 ; Sahra et al., 2021 ; Butt et al., 2019 ; Tseng et al., 2020 ; Zitelli et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported that chronic HEV infection might occur in HIV-infected patients and is associated with active hepatitis ( Dalton et al., 2009 ). There are also cases of HEV superinfection with hepatitis A, hepatitis B, hepatitis C, Campylobacter jejuni , Giardia intestinalis , or malaria, which indicates that HEV infection may exacerbate liver damage, accelerate disease progression, and increase mortality in patients with cirrhosis or chronic liver disease ( Lorenzo et al., 2016 ; Sahra et al., 2021 ; Butt et al., 2019 ; Tseng et al., 2020 ; Zitelli et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…3 Co-infection of hepatitis E and P. falciparum malaria are rarely reported in the literature. 4 This is the first reported case in Sri Lanka of a patient co-infected with both hepatitis E and P. falciparum malaria, and both infections were imported.…”
Section: Introductionmentioning
confidence: 90%